Vpliv sušenja titanovega gela na karakteristike kalciniranega TiO2 - Kanduč, Zoran (Kovine zlitine tehnologije, 1999)
Titanium(IV) oxide is used mostly as a pigmentand besides that for the advanced ceramics, catalysts, in electronic industry etc. ?$TiO_2$? is prepared by the sulphate and chloride processes. In Celje the former process is used. The characteristics of the products are influenced by the conditions in all stages of the technological process ant to a large extend by the calcination of the titanium gel. Understanding of the later process is important for the production control as well as in the case that different ?$TiO_2$? materials are desired. Titanium gels were taken from the industrial process and prepared in the laboratory. Samples were taken from the Moore filters, filter press and under the laboratory conditions they were dried also in vacuum at 25°C or by additional pressing and drying at 40 and 105°C. The samples were characterised by thermal analysis, SEM and XRD. The samples obtained by drying in vacuum exhibit larger particles and higher sintering. Results reveal that the characteristics of the end products can be influenced by the modifications in the drying stage.
Keywords: titanov dioksid; geli; kalcinacija